Prickle discomfort assessment of commercial knitted wool garments. Issue 1 (9th January 2018) - Naebe, Maryam; McGregor, Bruce; Dowling, Melanie; Tester, David
Abstract : Purpose: The purpose of this paper is to identify the significant factors important for prickle discomfort properties of commercial wool knitwear and to analyse information on variability of garments manufactured over two decades, a total of 177 purchased garments were tested. Design/methodology/approach: The relationship between the attributes of the reversed engineered garments and garment comfort, as assessed by Wool ComfortMeter, was determined. Findings: The results indicate that: mean fibre diameter had the most significant effect on prickle assessment; the coefficient of variation of fibre diameter interacted with fabric thickness in affecting prickle discomfort; and rib knit structures were pricklier than single jersey structures. Originality/value: The results provide objective evidence that the consumer surveys reporting dissatisfaction with the prickle discomfort of wool are based on real consumer experiences of prickle discomfort and are not based on "prejudice" against wool garments.